2015
DOI: 10.14687/ijhs.v12i1.3238
|View full text |Cite
|
Sign up to set email alerts
|

The challenges of the volunteerism process during international sport organizations/events

Abstract: Abstract:The purpose of this study was to explore the challenges of volunteers at various stages in their volunteering activities during international sport organizations/events and how these are interlinked with their personal benefits. This study also aimed to analyze the experiences of volunteers during the management process and their thoughts about volunteerism. The method applied in this study was qualitative in nature and the phenomenological approach was used. Data was collected by interviewing. "Purpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 4 publications
1
8
0
Order By: Relevance
“…Comparing the research results of our and other authors (Brusokas & Mikalauskas, 2019;Kerevičius, 2017;Laskienė & Anusauskaitė, 2008;Noordegraaf & Celebi, 2015;Schlesinger & Nagel, 2016), it can be stated that students are quite positive about volunteering activities in sport. Respondents of both genders had sufficient volunteering experience to reveal specific respondents' attitudes towards volunteering in sport.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Comparing the research results of our and other authors (Brusokas & Mikalauskas, 2019;Kerevičius, 2017;Laskienė & Anusauskaitė, 2008;Noordegraaf & Celebi, 2015;Schlesinger & Nagel, 2016), it can be stated that students are quite positive about volunteering activities in sport. Respondents of both genders had sufficient volunteering experience to reveal specific respondents' attitudes towards volunteering in sport.…”
Section: Discussionsupporting
confidence: 62%
“…According to the research conducted by Brusokas and Mikalauskas (2019), students are motivated by the desire to continue their involvement in sports. Noordegraaf and Celebi (2015) revealed that sport as a phenomenon remains a more important motive for males because they are not inclined to form emotional connections with other volunteers during volunteering. Anusauskaitė (2007) states that the desire to be among athletes as an important motive to participate in volunteering in sport was expressed almost equally by both females and males.…”
Section: Discussionmentioning
confidence: 99%
“…This reduces motivation to volunteer or even eliminates it at all. (McBride, Lough & Sherraden, 2010;Noordegraaf & Celebi, 2015;Oppenheimer, 2008;Pantea, 2012;Plagnol & Huppert, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, major sporting events are served mostly by "one-time" volunteers -people who don't have experience of successful volunteering as it is indicated by the author G. Pauline (Pauline, 2011). What is more the experts note that the main motivation for volunteerism in sport competitions is a variety of social benefits and career opportunities but it is not the love to the physical training and sports (Noordegraaf, & Celebi, 2015;Erturan-Ogut, 2014;Pauline, 2011). Moreover the role of volunteers is performed by the unauthorized persons who do not have practical experience of such activities but they do not even possess the knowledge about the sport and competitions in which they do the service support.…”
Section: Introductionmentioning
confidence: 99%